SUSCEPTIBILITY OF CYPRINID AND NON-CYPRINID FISH CELL LINES TO KOI HERPESVIRUS (KHV) - Tuti Sumiati; Agus Sunarto (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2009)
Koi herpesvirus (KHV) is an emerging virus that infects koi and common carp (Cyprinus carpio) with mortality up to 95% within 7 days. The disease is rapidly spreading worldwide including to Indonesia. However, it has only been documented in koi and common carp. The aim of this research was to evaluate the susceptibility of fish cell cultures originated from cyprinid and non-cyprinid fish to KHV. Koi Fin (KF-1) and Koi Tail (KT-2) cell lines derived from koi carp and SSN-1 cells originated from fry of striped snakehead were used in this study. The cells were inoculated with tissue extract of KHV-infected koi carp (experiment 1) and virus stock of KHV (experiment 2). The cultures were incubated at 22oC and the onset and type of cytophatic effect (CPE) were observed for 21 days post inoculation. The results of experiment 1 showed that CPE was observed in KT-2 at day 6 post inoculation. In the experiment 2, however CPE was observed in KF-1 and KT-2 cells at day 4 post infection. CPE was not observed in SSN-1 of either experiment 1 or experiment 2. CPE was characterized by extensive vacuolization of the infected cells. Polymerase chain reaction (PCR) assay of cell and tissue culture supernatants confirmed that KF-1 and KT-2 showing CPE were indeed infected with KHV. The results indicated that KF-1 and KT-2 cells were susceptible and SSN-1 was resistant to KHV. The implication of these findings was also discussed in the paper.